2022
DOI: 10.3390/v14081736
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation Analysis of Porcine Circovirus Type 4 in South China in 2019 to 2021

Abstract: Porcine circovirus type 4 (PCV4) is a novel virus associated with porcine dermatitis and nephropathy syndrome (PDNS)-like signs identified firstly in China in 2019. However, the details of the molecular epidemiology of PCV4 are unclear at this time. A total of forty-two related sequences were selected from the GenBank database to explore the spread of PCV4 and its rule in genetic evolution. Of the selected strains, 41 were from south China in 2019 to 2021 and the other was a foreign representative strain. Phyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…It is intuitive to exhibit the epitopes that are dominant in MHC genotypes. At the same time, bihierarchical clustering would reveal the cross-reactivity between different genotypes based on affinity analysis data ( 42 , 43 ). This intuitively reflects genotype proximity according to pathogen specificity, further understanding of susceptibility and resistance against pathogens in different races, geographies, populations, and even species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is intuitive to exhibit the epitopes that are dominant in MHC genotypes. At the same time, bihierarchical clustering would reveal the cross-reactivity between different genotypes based on affinity analysis data ( 42 , 43 ). This intuitively reflects genotype proximity according to pathogen specificity, further understanding of susceptibility and resistance against pathogens in different races, geographies, populations, and even species.…”
Section: Introductionmentioning
confidence: 99%
“…Alignment of variants has been implicated in many studies but is limited to the step of multiple sequence alignment, finding mutation sites, and exploring evolutionary clades ( 42 , 44 , 45 ). On this basis, another direction — further research on the impact of mutation sites — should also be taken into consideration.…”
Section: Introductionmentioning
confidence: 99%
“…Further investigation is required www.nature.com/scientificreports/ to establish the standardized criteria for genotyping PCV4, given the current paucity of sequence information. As mentioned above, previous reports showed that the amino acid at the position 27 of the Cap gene could be used as a marker to distinguish between PCV4a (27S) and PCV4b (27N) 19,20 . However, the results in this study showed that the amino acid residue at position 27 cannot be used to differentiate between PCV4a and PCV4b since the Thai PCV4b strains and the Korean PCV4b strains (KU-02010 and KU-02011) showed N27S (Fig.…”
Section: Genetic Characteristics Of Pcv4mentioning
confidence: 89%
“…This is in contrast with PCV2 genotyping that a unified classification scheme based on Cap gene was proposed 18 . For PCV4 genotyping, there have been several studies proposing different criteria and markers to differentiate PCV4 genotypes, such as 2-group classification (PCV4a and PCV4b) and 3-group classification (PCV4a, PCV4b, and PCV4c) 10,[19][20][21] . Among these studies, the residue at 27 and 212 of capsid gene were also proposed to be used in distinguishing PCV4a (27S and 212L) from PCV4b (27N and 212M) 19,20 .…”
Section: Genetic Characteristics Of Pcv4mentioning
confidence: 99%
See 1 more Smart Citation